Bioactive compounds and sensory analysis of freeze-dried prickly pear fruits from an inter andean valley in Peru - Choque Quispe, David (2023)
Prickly pear fruits are seasonal and have shades ranging from pale green to deep purple. Their pigments are associated with bioactive compounds, being sensitive to thermal transformation processes for their conservation. The objective of this research was to evaluate the bioactive compounds and the sensory analysis of freeze-dried prickly pear fruits from an inter-Andean valley in Peru. The prickly pear fruits of the morada, anaranjada, and blanca ecotypes came from an inter-Andean valley in Peru at 2972 m altitude. The sliced fruits were freeze-dried at 40 C and 0.25 mTorr, and the total polyphenol content (TPC), vitamin C, and antioxidant activity (AA) were determined, as well as the color L* a* b*, color index (CI*), FTIR spectra, and mineral content. In the same way, sensory analysis of preferences with nine scales was applied. It was observed that in the freeze-dried fruits, TPC, AA, and vitamin C increased significantly (p-value < 0.05), and their corresponding functional groups increased in intensity in their corresponding FTIR spectra; furthermore, trace elements such as Cu, Fe, Se, Zn, Si, and Mn were identified. On the other hand, freeze-drying provided deeper colors to the fruits, which most panelists said they “very much liked” during the sensory analysis, although the texture was not very well accepted, with most panelists reporting being “indifferent” towards it. The freeze-drying technique allows the bioactive and sensory attributes of prickly pear fruits from inter-Andean valleys to be preserved, making it a potential fruit for export and conservation due to its seasonality.